The molecular chaperone CCT modulates the activity of the actin filament severing and capping protein gelsolin in vitro - Svanström, Andreas (Cell Stress Chaperones, 2015)
The oligomeric molecular chaperone CCT is essential for the folding of the highly abundant protein actin, which in its native state forms actin filaments that generate the traction forces required for cell motility. In addition to folding proteins, CCT can provide a platform for protein complex assembly and binds actin filaments assembled in vitro. Some individual subunits of CCT, when monomeric, have been shown to be functionally active, and in particular, the CCTepsilon subunit is involved in the serum response factor pathway that controls actin transcription. Thus, there is a complex interplay between CCT and actin that extends beyond actin folding. CCT has recently been shown to bind gelsolin, an actin filament severing protein that increases actin dynamics by generating filament ends for further actin polymerization. However, the biological significance of the CCT:gelsolin interaction is unknown. Here, using a co-immunoprecipitation assay, we show that CCT binds directly to gelsolin in its calcium-activated, actin-severing conformation. Furthermore, using actin filaments retained from fixed and permeabilized cells, we demonstrate that CCT can inhibit the actin filament severing activity of gelsolin. As our work and that of others shows gelsolin is not folded by CCT, the CCT:gelsolin interaction represents a novel mode of binding where CCT may modulate protein activity. The data presented here reveal an additional level of interplay between CCT and actin mediated via gelsolin, suggesting that CCT may influence processes depending on gelsolin activity, such as cell motility.